Perbedaan Motivasi dan Kemampuan Berpikir Kreatif Mahasiswa melalui Multimedia Collaborative-Interactive - Fidianty, Ami; Hadi, T.S. (Universitas Muria Kudus, 2023)
This Study Aims To Apply Collaborative-Interactive Multimedia Learning In Order To Determine Differences In Students’ Motivation And Creative Thinking Skills. This Research Is Quantitative Research Using Experimental Research Methods In The Form Of Quasi-Experimental Design, Then The Type Is Mid-Respond And Post-Respond With Non-Equivalent Control Group Design. The Population In This Study Were All Civil Engeneering Students At X University. The Focus Of The Research Was On A Sample Of 38 A1 And 10 A2 Student In Mathematics III. Data Analysis Techniques In This Study Used Test, Questionnaires, And Observation. The Data Analysis Technique For Mid-Respond And Post-Respond Result In This Study Were Descriptive Statistics, Validity Test, Normality Test, And Different Test. The Result Of Study Showed That There Was No Difference In Motivation And Creative Thinking Skills Of Students Treated With Collaborative-Interactive Multimedia Learning With Students Who Did Not Receive The Learning Treatment. This Arises Because The Average Obtained Is Vulnerable To Almost The Same Or Not Much Different, Namely The Mid-Test Average Of 28,792 And The Post-Test Of 30,604. Howefer, By Observation, And Quetionnaires Showed That The Average Proportion Of Collaborative-Interactive Multimedia Learning Was Stated To Be Good, Namely 83,31% So That Collaborative-Interactive Multimedia Learning Had Affected Fluency And Flexible Indicators Of The Creative Thinking Skills. Then, The Average Proportion Of Questionnaires To Student Learning Motivation Was Obtained At 82,92% So That There Was A Contribution Of Collaborative-Interactive Multimedia Learning To Student Learning Motivation.